Koordinasi dalam Penyusunan Rencana Kebutuhan Barang Milik Daerah (Studi pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Madiun) - Wiyanika, Arina (Jurnal Ilmiah Administrasi Publik, 2021)
Local asset planning is a important beginning activity in asset management. Coordination needs to do asset management, include local asset planning. The study aims to know deeply how coordination of asset planning drafting and its obstacle factor with study at BPKAD in Madiun City. Data collection method include interview, observation, and literature review. Data analysis is descriptive qualitative. The result shows that coordination of asset planning drafting not optimal yet to make asset administrator in tune. It shows from repeat mistakes happen every local asset planning drafting. This affect lateness of determination of asset planning report. Obstacle factor of coordination of asset planning drafting are ability and understanding of asset administrator and not available yet of application and standard of asset planning.